Dead Collections - Mary Snyder Broussard (Partnership: The Canadian Journal of Library and Information Practice and Research)
Isaac Fellman’s Dead Collections: A Novel (2022) portrays a fictional archivist Sol, who experiences chronic illness in the form of vampirism. While he experiences many symptoms including cold skin and reliance on weekly blood transfusions, it is his life-threatening photophobia (aversion to sunlight) that becomes a serious impairment to commuting to and from work. While Sol and his vampirism are clearly works of fiction, the novel accurately depicts working in libraries with a chronic illness. This article compares and connects the fictional story in Dead Collections to the growing body of literature on library workers with disabilities and chronic illness, particularly articles that give voice to those with relevant lived experiences. Highlights of this discussion include the topics of non-apparent illnesses, disclosure, passing, reactions to disability among coworkers and supervisors, and the promises and disappointments of the Americans with Disabilities Act.